Perception of The Leadership Behaviour on Job Satisfaction Among Registered Nurses - Bit-Lian, YEE; TAN Woei-Ling; Bryant Tan Cyan-Yng (Talenta Publisher, 2021)
There are many factors, and one of the factors influencing job satisfaction is leadership behavior. The purpose of this study is to determine the association between socio-demographic and the leadership behavior of nurse managers on job satisfaction based on the perception of registered nurses in a selected private hospital, Malaysia. A crosssectional descriptive study involving 161 registered nurses using convenient sampling with self-administered questionnaires and using Leadership Behaviour Description Questionnaire (LBDQ) and Minnesota Satisfaction Questionnaire (MSQ). There was no significant correlation between socio-demographic data and job satisfaction with the Pearson correlation of (r < 0.3, p > 0.05). However, the result showed that there was statistically significant between leadership behaviour and job satisfaction with (p < 0.05, r = 0.572, p = 0.000 and r = 0.531, p = 0.022). Leadership behavior serves as an important aspect in nursing to determine job satisfaction and address nurse shortage issues in the future. Hence, staff development and monitor the leadership behavior among the staff to provide them a piece of measurable concept pertaining to leadership behavior at least to let them understand their progress to becoming an effective leader.